Growth optimization of escherichia coli harboring superoxidase dismutase using response surface methodology / Atikah. 0. ... [et al.] - 0., Atikah; M., Rosfarizan; A.R., Raha; A.B., Ariff (2008)
A preliminary study on the Response Surface Methodology (RSM) was employed to optimize the growth of recombinant E. coli BL21 (DE3) pLysS (ESOD) harboring superoxide dismutase (SOD) on three variables (nitrogen source, carbon source and initial pH) in shake flask cultures. Full Factorial Design (FFD) was applied as a screening method to the independent variables, and maximum cell concentration (Xmax) achieved was 3.59g/L at a combination of 7 C/N and initial pH of 7.5. The combined effect of each variables and optimized condition were obtained using Central Composite Design (CCD). The optimized nitrogen and carbon sources derived from the RSM regression were 21.86g/L and 4.89g/L, respectively. The optimal initial pH of the medium was 7.84. The highest cell concentration achieved based on the model developed from RSM was 7.39g/L, which compared very well with the maximum predicted value.